Rheumatische Erkrankungen mit typischer Erstmanifestation im jungen Erwachsenenalter - Max, Regina; Blank, Norbert; Lorenz, Hanns-Martin (Der Internist, 2012)
Inflammatory rheumatic diseases can occur at any age. In young adulthood spondyloarthritis and systemic lupus erythematosus in particular present the first symptoms. General practitioners and internists are the first to be contacted by patients. They should be familiar with inflammatory back pain, HLA B27, inflammatory signs in the sacroiliac joints on imaging and extra-articular manifestations in order to transfer patients suspected of having spondyloarthritis to a rheumatologist. The same applies to skin and organ involvement, especially lupus nephritis, in patients with suspected systemic lupus erythematosus, as well as antibody screening in particular for antinuclear antibodies and anti-double stranded DNA (dsDNA) antibodies. Patients are often at the beginning of their professional and family career, therefore, early diagnosis is necessary to initiate an adequate therapy and prevent or minimize long-term damage.